O governo da infância: práticas de alfabetização no Estado da Bahia - Pereira, Reginaldo Santos (Universidade Federal de São Carlos, 2015)
This study aimed to analyze how the curricular system present in a literacy proposal governs and produces children's subjectivities in the early years of elementary school in the state of Bahia. The survey was conducted based on the analysis of the Covenant Program for Education (PPE) established in 2012 by Bahia s Secretariat of Education in municipal and state schools of participant municipalities. The PPE s documents analyzed are: the Didactic Proposal for Literacy, the book of children's stories It seems to be... but it is not, the Activity Book and the kit of teaching materials. As a methodological tool we used the arqueogenealogy of Michel Foucault, with the aim of understanding the relations between knowledge and power that surround the discursive and non-discursive practices which produce forms of subjectivity in both reading and writing activities, as in children's literature. The research results revealed that the curricular structure of the analyzed documents acts as a device of knowledge, power, and subjectivity and it is based on the constructivist theoretical frameworks of the Written Language Psychogenesis. The literacy practice is also based on the stories of children's literature, which play the role of taming the imaginary, producing disciplinary and subjective effects on children. Therefore, the process of childhood governmentalisation underway in the state of Bahia discursively produces an essentialist, disciplined, stagiest and normalized childhood. Finally, the study sought to weave itineraries that allow to question and to expand the knowledge about literacy, curriculum, and the arts of governing childhood.
Keywords: Alfabetização; Currículos; Governo; Infância; Curriculum; Literacy; Government; Childhood; CIENCIAS HUMANAS::EDUCACAO